2006
DOI: 10.1002/chin.200640058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pentalene Systems Employing a Sequence of Pauson—Khand Reaction, Michael Reaction, and Desilylation.

Abstract: Cyclopentane derivativesCyclopentane derivatives Q 0030 Synthesis of Pentalene Systems Employing a Sequence of Pauson-Khand Reaction, Michael Reaction, and Desilylation. -The reaction sequence is applied to norbornene, norbornadiene and pentadiene. The resulting products are further desilylated [cf. (V)] or alkylated followed by desilylation. -(BECHEANU, A.; BELL, T.; LASCHAT, S.; BARO, A.; FREY, W.; STEINKE, N.; FISCHER, P.; Z. Naturforsch., B: Chem. Sci. 61 (2006) 5, 589-596; Inst. Org. Chem., Univ. Stuttgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…One reason for the paucity of dicobalt-promoted [4 + 2] cycloaddition examples is the high propensity for PKR to occur. {Co 2 (CO) 6 }–alkyne complexes are known to undergo facile intermolecular PKR with dienes. , Moreover, acyclic dienyne dicobalt hexacarbonyl complexes were shown to prefer PKR over dicobalt-promoted intramolecular [4 + 2] cycloadditions . In our studies, dicobalt promoted transannular [4 + 2] cycloaddition reactions showed impressive selectivity, and no transannular PKR products 28 , 29 , or 30 were detected (Scheme ).…”
mentioning
confidence: 52%
“…One reason for the paucity of dicobalt-promoted [4 + 2] cycloaddition examples is the high propensity for PKR to occur. {Co 2 (CO) 6 }–alkyne complexes are known to undergo facile intermolecular PKR with dienes. , Moreover, acyclic dienyne dicobalt hexacarbonyl complexes were shown to prefer PKR over dicobalt-promoted intramolecular [4 + 2] cycloadditions . In our studies, dicobalt promoted transannular [4 + 2] cycloaddition reactions showed impressive selectivity, and no transannular PKR products 28 , 29 , or 30 were detected (Scheme ).…”
mentioning
confidence: 52%